Hybrid cell line development system utilizing site-specific integration and methotrexate-mediated gene amplification in Chinese hamster ovary cells - Min, Honggi; Kim, Seul Mi; Kim, Dongwoo; Lee, Solhwi; Lee, Sumin; Lee, Jae Seong (Frontiers in Bioengineering and Biotechnology, 2022)
Site-specific integration has emerged as a promising strategy for streamlined and predictable Chinese hamster ovary (CHO) cell line development (CLD). However, the low specific productivity of the targeted integrants limits their practical application. In this study, we developed a hybrid CLD platform combining site-specific integration of a transgene and dihydrofolate reductase/methotrexate (DHFR/MTX)-mediated gene amplification to generate high-producing recombinant CHO cell lines. We used the CRISPR/Cas9-based recombinase-mediated cassette exchange landing pad platform to integrate the DHFR expression cassette and transgene landing pad into a CHO genomic hot spot, C12orf35 locus, of DHFR-knockout CHO-K1 host cell lines. When subjected to various MTX concentrations up to 1 μM, EGFP-expressing targeted integrants showed a 3.6-fold increase in EGFP expression in the presence of 200 nM MTX, accompanied by an increase in the DHFR and EGFP copy number. A single-step 200 nM MTX amplification increased the specific monoclonal antibody (mAb) productivity (qmAb) of mAb-producing targeted integrants by 3-folds, reaching a qmAb of 9.4–12.1 pg/cell/day. Fluorescence in situ hybridization analysis showed colocalization of DHFR and mAb sequences at the intended chromosomal locations without clear amplified arrays of signals. Most MTX-amplified targeted integrants sustained mAb production during long-term culture in the absence of MTX, supporting stable gene expression in the amplified cell lines. Our study provides a new CLD platform that increases the productivity of targeted integrants by amplifying the transgene copies.